Evaluation of Performance Metrics Required in Proper Selection of SDN Controller for Integrated Satellite-Terrestrial Networks - Oluwatobi A. Ayofe; Mu'azu J. Musa; Zanna M. Abdullahir; Abdoulie M.S. Tekanyi; Aliyu D. Usman; Ezekiel E. Agbon; Emmanuel A. Otsapa; Agburu O. Adikpe; Matthew Iyobhebhe; Paul Thomas Muge (Pakistan Journal of Engineering & Technology)
SDN controllers are increasingly becoming an integral part of modern communication networks due to their ability to centrally control and manage networks from a global point of view. One of the application areas in which the SDN paradigm is gaining traction is the Integration of Satellite and Terrestrial Networks (ISTN). Considering that there are different SDN controllers with their intrinsic characteristics, which translate to different performance characteristics, it is pertinent to determine the SDN controllers that will be most suitable for the specific application area. This study embarked on evaluating selected SDN controllers that will help in making informed selection decisions for suitability in a future ISTN architecture. Five SDN controllers were subjected to evaluation and they are Open Network Operating System (ONOS), Opendaylight (ODL), Floodlight (FL), Ryu, and Pox. These controllers are evaluated based on throughput and latency metrics, which are considered some of the factors that could influence the performance of the interworking of both terrestrial and satellite networks. The controllers were subjected under various topologies and traffic densities which are (i) single topologies under no cross traffic, half-bandwidth cross traffic, and high-bandwidth cross traffic conditions (ii) linear topology under no cross traffic, half-bandwidth cross traffic, and high-bandwidth cross traffic conditions (iii) tree topology under no cross traffic, half-bandwidth cross traffic, and high-bandwidth cross traffic conditions (ii) linear topology under no cross traffic, half-bandwidth cross traffic, and high-bandwidth cross traffic conditions (iii) tree topology under no cross traffic, half-bandwidth cross traffic, and high-bandwidth cross traffic conditions. Under all conditions, ONOS shows superiority in terms of throughput while Ryu shows superiority in terms of synchronization time. Focusing specifically on the tree topologies, considering it follows the same pattern with the single and linear topologies, the ONOS exhibited throughput of 815flow/ms under no cross traffic and throughput of 807flow/ms under both half-bandwidth and high-bandwidth band cross traffic. Ryu exhibited a synchronisation time of 19ms, 23ms, and 26ms under the no cross traffic, half-bandwidth cross traffic, and high-bandwidth traffic cross-traffic conditions, respectively. Observing from the values for both the throughput and synchronisation time metrics under all the topologies, it can be inferred that a number of hosts have more impact on the metrics rather than traffic volume, and this could be attributed to caching mechanisms like Address Resolution Protocol (ARP) wherein new traffic from known hosts can quickly be processed compared to new traffic from new hosts. In summary, the ONOS controller can be considered to offer good performance in an ISTN.